Athar al-IslÄm fÄ« Taá¹awwuri MaâÄnÄ« al-AlfÄáºi fi al-Lughah al-âArabiyyah (Al-Jamiah Research Centre, 2003)
Language is one of the distinguishing factors between human and other creatures in the universe. It is also the identity of a society as there is no society without a language. Both language and society have close relationship that could not be separated as they are interrelated. Every single change in any society has a certain effect ot its language, either in its words or in its meanings. This is also happened to Arabic in the Arab world. Islam that came to the Arabs brought about some significant change in their faith, religious services, attitude and also some other new traditions. To articulate all these new things, the social construct some new terms that are adapt from the existing language by some process, i.e., changing, shifting, broadening and even narrowing the meaning. However, those changes did not remove the original meaning of a word. It means that, many times, a word has two meaning which we knows later as etymological and terminological meanings. This article tries to reveal those changes and distinguish the pattern of the charge.